A rare case of cephalothoracopagus janiceps conjoined twins - Seda Yılmaz-Semerci; Tevfik Güzelbey; Dilek Kurnaz; Şahin Kalkan; Merih Çetinkaya (The Turkish Journal of Pediatrics)
Conjoined twins represent a rare phenomenon of a monochorionic monoamniotic twin. Five types of conjoined twins have been described and thoracocephalopagus was reported to be seen with an incidence of 1 in 3 million. The etiology has not been elucidated yet. Therefore, more data is required to understand this entity better. Herein, we report a case of thoracocephalopagus.